Screening for autonomic neuropathy using validated non-invasive scale among diabetes patients treated in the selected primary health centres of Puducherry, India: an operational research - Thekkur, Pruthu; Muruganandam, Vignesh; A., Narayan K.; Boovaragasamy, Chithra (International Journal Of Community Medicine And Public Health, 2019)
Background: Diabetes autonomic neuropathy (DAN) is a complication of diabetes which has direct implications on the mortality of diabetes patients. American Diabetes Association (ADA-2017) guidelines recommend early recognition and treatment of DAN. In this regard, we conducted a study among diabetic patients treated in the selected PHCs of Puducherry to determine the proportion with DAN and to assess the factors associated with DAN. Methods: A cross-sectional analytical study was conducted among diabetics and information on socio-demographic details, morbidity and behavioural risk factors were elicited using semi-structured interview schedule. The COMPASS-31 questionnaire was administered to assess the autonomic neuropathy symptoms. The data was captured using EpiCollect mobile app and analysed using Stata 12.0 software. The proportion of DAN was expressed as percentage with 95% confidence interval. The association between independent factors and DAN was assessed using multivariate generalized linear models. The prevalence ratio with 95% CI was used to express the strength of association. Results: Of the total 303 individuals with diabetes, 32 {10.6% (95% CI: 7.3%-14.6%)} were screened positive for autonomic neuropathy using COMPASS-31 scale. The number of individuals with diabetes who needed to be screened (NNS) for finding one with autonomic neuropathy was 10 (303/32). Conclusions: One in ten individuals with diabetes was screened positive for autonomic neuropathy. With good yield, there is need for including autonomic neuropathy screening as a component in the comprehensive care provided to diabetes patients in the primary health centres.